Modification of the endoscopic management of congenital duodenal stenosis - Asabe, Koushi; Kawarabayashi, Tatsuhiko; Yoshizato, Toshiyuki; Nagakawa, Kentaro; Yukitake, Ko; Yokoyama, Masanori; Tsutsumi, Makoto; Hoshino, Seiichiro; Oka, Yoichiro; Shirakusa, Takayuki (The Turkish Journal of Pediatrics, 2008)
This report documents a new endoscopic management modality for congenital membranous stenosis in the third portion of the duodenum. Standard approaches to duodenal stenosis in newborns include a laparotomy with an enteroenterostomy, bypassing the obstruction, or a duodenoduodenostomy with excision. We successfully developed a modification of the endoscopic treatment modality for congenital duodenal diaphragm.